UNIT 12.40 Visualization of Telomere Integrity and Function In Vitro and In Vivo Using Immunofluorescence Techniques. Issue 1 (1st July 2015) - Cesare, Anthony J.; Heaphy, Christopher M.; O'Sullivan, Roderick J.
Abstract : In cancer cells, telomere length maintenance occurs largely via the direct synthesis of TTAGGG repeats at chromosome ends by telomerase, or less frequently by the recombination‐dependent alternative lengthening of telomeres (ALT) pathway. The latter is characterized by the atypical clustering of telomeres within promyelocytic leukemia (PML) nuclear bodies, which harbor proteins that are linked with DNA repair and recombination activity. For this reason, it is speculated that these associated PML bodies represent the sites of the recombination that maintains telomere length. The protocols described here can be employed for the routine investigation of the structural integrity of telomeres and the association of proteins at telomeres in normal cells, challenged cells, and archived formalin‐fixed paraffin‐embedded clinical tissue specimens that may have activated the ALT pathway. © 2015 by John Wiley & Sons, Inc.